Photographic photometry and minima timings of the eclipsing binaries U Sge and V363 Cyg - Pikhun, A. I. (Одеські астрономічні публікації, 2017)
Seven seasonal minima timings of U Sge and 5 moments of weakenings of V393 Cyg obtained from the photovisual observations using the Odessa 7-camera astrograph plate collection are listed. The tables of observations are available via Internet at http: / /uavso.pochta.ru/pikhun